Smelter Fumes, Local Interests, and Political Contestation in Sudbury, Ontario, during the 1910s - Munton, Don; Temby, Owen (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2015)
During the second half of the 1910s the problem of sulphur smoke in Sudbury, Ontario, pitted farmers against the mining-smelting industry that comprised the dominant sector of the local economy. Increased demand for nickel from World War I had resulted in expanded activities in the nearby Copper Cliff and O’Donnell roast yards, which in turn produced more smoke and destroyed crops. Local business leaders, represented by the Sudbury Board of Trade, sought to balance the needs of the agriculture and mining-smelting sectors and facilitate their coexistence in the region. Among the measures pursued, farmers and some Board of Trade members turned to nuisance litigation, with the objective of obtaining monetary awards and injunctions affecting the operation of the roast yards. While the amounts of the awards were disappointing for the farmers, the spectre of an injunction was sufficient to convince the provincial government to ban civil litigation in favour of an arbitration process accommodating industry. This article provides an account of the political activism over Sudbury’s smoke nuisance that failed to bring about emission controls, highlighting the contextual factors contributing to this failure.